Ad hoc network - Kelsie Nabben; Ellie Rennie (Internet Policy Review, 2022)
There is no one set definition for the phrase “ad hoc networks”. The term refers to the ability for members of a network to establish a network connection between devices. Ad hoc networks are relevant both in technical terms of certain network infrastructures, as well as in terms of the social, political and economic modes of self-organisation they enable. This requires people to combine software and hardware tools to set up peer-to-peer infrastructure that provides access to temporary information networks, as well as networking standards and policy frameworks. When long-standing, these can adapt to become local area networks. An example of an ad hoc network is a temporary cryptocurrency economy, such as a Decentralised Autonomous Organisation, which can connect people, information, and resources online and in person for a specific purpose.